PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN - Deswara, Nabila Putri; Krisnawati, Astrie; Saraswati, Rr. Sri (2021)
Industry has an important role for national economic growth. Where, the company has a goal to get a good profit in order to be able to create good financial performance. Companies are considered not only limited to their financial performance, but companies are also expected to have good management in the form of Good Corporate Governance (GCG). The research was carried out with the aim of knowing how the influence of GCG which is proxied by institutional ownership on financial performance as proxied by Return on Assets (ROA). In this study, there were 8 food and beverage sub-sector companies listed on the IDX for the 2015-2019 period which were sampled. Panel data regression analysis is the data analysis technique in this study. This study explains that institutional ownership does not have a significant effect on financial performance.